2017
DOI: 10.1038/ncomms15680
|View full text |Cite
|
Sign up to set email alerts
|

In vitro differentiation of human embryonic stem cells into ovarian follicle-like cells

Abstract: Understanding the unique mechanisms of human oogenesis necessitates the development of an in vitro system of stem cell differentiation into oocytes. Specialized cell types and organoids have been derived from human pluripotent stem cells in vitro, but generating a human ovarian follicle remains a challenge. Here we report that human embryonic stem cells can be induced to differentiate into ovarian follicle-like cells (FLCs) in vitro. First, we find that two RNA-binding proteins specifically expressed in germ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
3

Relationship

3
7

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 45 publications
2
97
0
Order By: Relevance
“…Quantitative real‐time PCR (q‐PCR) analysis was carried out as previously described (Jung et al., ). The specific primers used in q‐PCR analysis are listed in Table S3.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative real‐time PCR (q‐PCR) analysis was carried out as previously described (Jung et al., ). The specific primers used in q‐PCR analysis are listed in Table S3.…”
Section: Methodsmentioning
confidence: 99%
“…We examined the ability of hiSCs to sustain mouse spermatogonia cells because of the inaccessible procurement of human spermatogonia cells from hospitals. Previous studies performing xenotransplantation experiments transplanting primate spermatogonia stem cells into mouse testis demonstrated that primate germ cells colonized in the seminiferous tubules of the recipient mice, but the primate germ cells did not differentiate because of the evolutionary differences between these species 50 . The isolated mouse spermatogonia cells in our study attached and survived on the hiSCs, but no differentiated spermatocytes were detected (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…195 However, with regard to hESCs, development of structures resembling primary ovarian follicles was the most advanced stage of differentiation that could be reached. 196…”
Section: Generation Of Oocytes From Embryonic and Induced Pluripotentmentioning
confidence: 99%